BALINESE MINORITY VERSUS SASAK MAJORITY: MANAGING ETHNO-RELIGIOUS DIVERSITY AND DISPUTES IN WESTERN LOMBOK - Budiwanti, Erni (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2014)
Research upon inter-ethnic and inter-religious relation strongly marked with disparities and conflict are much more extensively done (see Suprapto, 2013, Telle, 2013, Balitbang depag 2006) compared to that of the study on peace and harmony. In other words, analytical reports on inter-religious tolerance and harmony are still relatively rare or less conducted than the one which con¬centrates more on social conflict. Without intentionally denying the importance of conflict and dispute in the inter ethno-religious studies, this paper tries to focus on the problem of how to maintain social harmony and peace between two groups coming from different ethnic and religious backgrounds. The analysis will particularly look at ritual performances: Puja Wali and Perang Topat hedl annually at Lingsar village, Lingsatrsub-district of West Lombok regency. These ceremonial events have so far been very vital especially in promoting and creating a social atmosphere that upholds mutual-tolerance, mutual-recognition, and mutual respect between the Hindu-Balinese and the Muslim Sasak. Long term sustainability of these ritual activities proves that in addition to, the conflict, harmony, based on the spirit of living co-existently in peaceful circumstances, undeaniably becomes an important part of everyday living reality.